The Mediator Role of Anger in The Relationship Illegitimate Tasks and SME Employee´s Turnover: Empirical Evidences from Developing Nation - Aamar Ilyas; Jose Moleiro Martins; Ramraini Ali Hassan; Mario Nuno Mata; Joao Xavier Rita; Anabela Batista Correia; Pedro Neves Mata (Allied Business Academy, 2021)
Illegitimate tasks cause a threat to employees' job security; as a result, increasing the stress level. The purpose of this research is to explore how illegitimate tasks determine SME employees' turnover intentions and investigate the mediating role of anger in sustaining this relationship. A structured interview questionnaire was used for data collection from volunteering employees of manufacturing SMEs of Gujranwala city. Structural Equation Modeling (SEM) and Partial Least Square (PLS) software were used to analyze the data. Data analyzed in two steps: first, to check the goodness of measures through reliability and validity of constructs. In the second step, to assess the hypothesis of this study with the help of the structural model. The results indicate that illegitimate tasks positively influence both employees' turnover intentions and their anger level. The findings show all relationships were statistically significant. Lastly, this study's finding shows that anger has successfully mediated the relationship between illegitimate tasks and SME employees' turnover intention.